2011
DOI: 10.1007/s10709-011-9574-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effects of inbreeding on lifespan and starvation resistance in Drosophila melanogaster

Abstract: Because of their decreased overall fitness and genetic variability inbred individuals are expected to show reduced survival and lifespan under most environmental conditions as compared with outbred individuals. Whereas evidence for the deleterious effects of inbreeding on lifespan has been previously provided, only a few studies have investigated effects of inbreeding on survival under starved conditions. In the present study we compared the abilities of inbred and outbred adult Drosophila melanogaster to surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 108 publications
(125 reference statements)
1
4
0
Order By: Relevance
“…We show that in a natural population of the ant F. exsecta, inbreeding does not translate into higher mortality upon starvation, which is consistent with previous findings in D. melanogaster [17,50,51]. In agreement with this, inbreeding did not significantly affect the expression of 8 of the 10 genes studied.…”
Section: Discussionsupporting
confidence: 92%
“…We show that in a natural population of the ant F. exsecta, inbreeding does not translate into higher mortality upon starvation, which is consistent with previous findings in D. melanogaster [17,50,51]. In agreement with this, inbreeding did not significantly affect the expression of 8 of the 10 genes studied.…”
Section: Discussionsupporting
confidence: 92%
“…A growing number of empirical studies have reported that inbreeding may have profound impact on the fitness-related traits of insects [7]. Inbreeding can have strong negative effects on fitness at all life stage, including larval development time [8], [9], survival [10], [11], adult body size and mass [12], [13], [14], adult lifespan [12], [15], fecundity [15], [16], [17], fertility [18], [19], [20], and even immune function [21]. So far, inbreeding depression has been quantified across a range of fitness-related traits in only a limited number of insect species, for example, fruit flies [10], [16], [20], [22], flour beetles [15], [23], seed beetles [8], [11], [17], [24], and field crickets [4], [18], [21], [25], [26].…”
Section: Introductionmentioning
confidence: 99%
“…colonies was conducted firstly to mimic a natural setting, where flies frequenting a single cadaver are likely to be related [37], and secondly to observe any developmental differences. Whilst developmental differences have been noted in D. melanogaster [38] this was after thirty generations of inbreeding; far more than conducted here, which resulted in no differences in development. The purpose of correlating morphological development to percentage age, both through the lifecycle and the pupal stage, was to facilitate comparison between species and populations, as well as the use of the same data across a large temperature range.…”
Section: Discussionmentioning
confidence: 64%